Toleransi yang Bijak sebagai Solusi Islam dalam Menyikapi Pluralitas - Eka Syahriani; Abd Rahman R; Kurniati Kurniati (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
Humans live in plurality, which is an unavoidable phenomenon that can encourage conflict and has the potential to divide people. To realize unity based on existing differences, one of the values that must be upheld is the value of tolerance. This research aims to find out Islam's attitude towards plurality, what kind of tolerance is taught, and examples of its implementation. This research is qualitative literature research with a normative theological approach. The results of the research show that Islam's attitude towards plurality is to apply wise tolerance, not the excessive tolerance that is often applied in Indonesia. Wise tolerance means responding to religious plurality with each party continuing to follow its religion, upholding the principles of faith, which are the most basic things in religion, and not disturbing the existence of other parties. It is hoped that with wise tolerance, people can live in peace and tranquility without having to sacrifice the principles of faith that are embedded in their religion.